PERAN HUKUM DALAM PENINGKATAN KESEJAHTERAAN MELALUI EKONOMI BERBASIS KEADILAN: Role Of Law In Enhancing Welfare Through A Justice-Based Economy - Merdiani, Wentri; Ruslina, Elli (Fakultas Hukum Universitas Komputer Indonesia, 2025)
Social justice is a fundamental principle in achieving welfare as mandated by Pancasila and the 1945 Constitution. However, socio-economic inequality and uneven wealth distribution remain significant challenges in Indonesia. This study aims to analyze the role of law in supporting welfare improvement through a justice-based economy. Using normative research methods and a qualitative approach, this study evaluates legislation, government policies, and relevant legal practices in realizing social justice principles. The findings indicate that law plays a strategic role in reducing social inequality and ensuring equitable wealth distribution through policies such as agrarian reform, progressive taxation, MSME empowerment, and workers' rights protection. However, the implementation of these policies is often hindered by weak law enforcement, bureaucratic inefficiency, and corruption. Strengthening law enforcement, reforming bureaucracy, and increasing community involvement in policy oversight are crucial steps. This study highlights that synergy between the government, private sector, and society is necessary to create a legal system that supports an inclusive and socially just economy.